Factors associated with body image dissatisfaction of the elderly who practice weight training - Daniel Vicentini de Oliveira; José Roberto Andrade do Nascimento Júnior; Caio Rosas Moreira; Sônia Maria Marques Gomes Bertolini; Alessandra Regina Carnelozzi Prati; Cláudia Regina Cavaglieri (Editora Champagnat, 2018)
Abstract Introduction: The body image is a multidimensional construct of the internal and external representations of the corporal structures added to the physical appearance, which can be influenced by aging. The weight training can be an important exercise to help elderly to face all the changes arising from aging, being one of them the dissatisfaction with body image. Objective: This study aims at identifying the factors associated with body image dissatisfaction of the elderly who practice weight training. Methods: This is an observational cross-sectional study. The sample, chosen by convenience and intentionally, embraced 174 male and female elderly subjects who practice weight training at one of the 15 fitness centers drawn for the research that offered this modality of physical exercise in Maringá city, state of Paraná, Brazil. A questionnaire with sociodemographic and health profile questions was used, as well as the BSQ to assess body dissatisfaction. Data analysis was carried out by using a descriptive inferential statistical approach with the Chi-squared test, Fischer's exact test, and binary logistic regression, adopting a significance when p < 0.05. Results: The majority of the elderly showed no body dissatisfaction (82.2%). There was a significant association among the absence of body dissatisfaction and the following items: retirement (p = 0.031), current study (p = 0.035), self perception of health (p = 0.016), body self perception (p = 0.001), and practice time (p = 0.027). Conclusion: Based on the results obtained, it can be concluded that the sociodemographic factors are intervenient when considering body dissatisfaction of the elderly people who practice weight training.